Surface Ocean Hydrographic Changes in the Western Pacific Marginal Seas Since the Early Holocene - Pan, Hui-Juan; Chen, Min-Te; Kong, Deming; Lin, Xiaopei; Wong, Kuo-Tsan; Tsai, Hung-Ling; Liu, Shengfa; Shi, Xuefa; Yokoyama, Yosuke (Frontiers in Earth Science, 2020)
Climatic changes in the western Pacific marginal seas are influenced by global forcing and regional processes, including monsoons and ocean circulation. To better understand the process of hydrographic and temperature changes, we applied the UK’37 as our index of Sea Surface Temperature (SST) and TEX86 as the index of Subsurface Water Temperature (SWT) for the last 8400 years using the sediment core MZ01 from the continental shelf of the East China Sea (ECS). To focus on centennial and millennial variabilities, the original SST and SWT are filtered with the Ensemble Empirical Mode Decomposition (EEMD) of the Hilbert-Huang Transform (HHT), with the confidence defined by a new method, the Continuity Superposition Error Calculation Method (CSECM). The SST and SWT both have a quasi-period of 1000-2000 years, exhibiting some teleconnection with the north Atlantic climatic changes. The SWT decreased during approximately 6-4 ka and then increased by ~4°C to the late Holocene, almost anti-phase with the SST. The stronger Asian winter monsoon and China Coastal Current (CCC), are very likely responsible for the decreased SST in the late Holocene. In contrast, the increased SWT may imply that the stronger CCC has brought more Changjiang Diluted Water (CDW) southward and formed a thicker barrier layer in the ECS, which dampened bottom water heat loss that was transported from the Taiwan Warm Current (TWC) and Western Kuroshio Branch Current (WKBC). This process is tested by the hosing experiment that supports stronger stratification when the north Atlantic cooled. The combined results by UK’37 and TEX86 provide a new insight into the interaction mechanism among the winter monsoon, precipitation and the Kuroshio Current, and also raises caution to take more regional factors into account in the application of TEX86.